Fourier Coefficients of a Class of Eta Quotients of Weight 4 - Kendirli, BarÄ±ÅŸ (International Journal of Advanced Mathematical Sciences, 2016)
Recently, there have been several works on the coefficients of the Fourier series expansions of a class of eta quotients by Williams, Yao, Xia and Jin, Kendirli, and Alaca. Some important explicit formulas have been discovered. Williams expressed all coefficients of one hundred and twenty-six eta quotients in terms of Â and Â and Yao, Xia and Jin, following the method of proof of Williams, expressed only even coefficients of one hundred and four eta quotients in terms of Â and Â The author has expressed the even and odd coefficients of the Fourier series expansions of a class of eta quotients in terms of Â and Â for Â Meanwhile, Alaca has obtained the coefficients of the Fourier series expansions of a class of eta quotients in Â in terms of Â and Â Here, we will express the coefficients of the Fourier series expansions of a class of eta quotients in Â in terms of Â and Fourier coefficients of the four eta quotients.